Effects of organized exercise program within pre-school institution on postural status of children - Drljačić, Dragana (PONS - medicinski časopis, 2016)
Aim. Although pre-school age is characterized by accelerated growth and motor development, pre-school children spend most of their day in the kinder garden. It has been shown that the application of systematical exercise program is of utmost importance for child’s proper development. Considering that once acquired habits are hard to correct, monitoring of morphological, motor and postural status and continuous efforts aimed on their improvement are of great importance when working with pre-school children. Therefore, the aim of this study was to investigate the effects of organized exercise program on postural status of pre-school children. Methods. Postural status of fifty two children (30 boys and 22 girls) was estimated on two occasions separated by 12 months, using method of Napoleon Wolanski. At the time of the initial assessment children were 5.0 ± 0.5 years old. Results. Significant improvements in postural status were observed only in 4 of 8 evaluated segments. They included significantly better positioning of head (z = -2,12, p ˂ 0,05, r = 0,21), shoulders (z = -2,67, p ˂ 0,01, r = 0,26), scapulae (z = -2,67, p ˂ 0,01, r = 0,26) and leg shape (z = -2,33, p ˂ 0,05, r = 0.23). Conclusion. The obtained findings suggest that organized exercise programs need to be applied from the earliest age in order to ensure positive influence not only on preservation of good posture but on correction of functional deformities that later in life might have a negative influence on individuals health as well. Key words: posture, pre-school age, deformities